Lung nodule detection using template matching and similarity measurement [Şablon eşleme ve benzerlik ölçüm yöntemleri ile akciǧer nodül tespiti] - (:unkn) unknown (My University, 2010)
In this study, we developed a computer aided detection system (CAD) to detect lung nodules on computed tomography images. Template matching and similarity measurement methodsused for examine whether region of interest which extracted using image pre-processing techniques are nodule candidate.Intensity thresholding, distance thresholding, neighbourhood analysis are preprocessing techniques of the developed CAD system. Pearson's correlation coefficient, simple matching coefficient, Jaccard's coefficient, Euclidean Distance and Sokal & Sneath similarity coeeficient calculated to measure similarity between nodule candidate and the template. Sensitivity of the CAD and number of false positives per slice are given in conclusion. ©2010 IEEE.